Elite athletes` travel behaviour to/from sport events: A case study of biathlon - Lerho, M. (Mid Sweden University, Faculty of Human Sciences, Department of Health Sciences, 2024)
This thesis analyses how elite athletes travel to/from sport events and which barriers prevent them from engaging in a more sustainable travel behaviour. For this purpose, unstructured interviews with elite athletes were conducted to gain an in-depth understanding about travel experiences and decision-making from elite athletes` perspective. The sport of biathlon, which combines cross-country skiing with rifle shooting, was used as a case study. The analysis revealed that biathletes engage in frequent and extensive travelling, and that their most-used modes of transportation are road and air transportation. Travel arrangements were found to be usually taken care of by national federations and not by biathletes themselves. Moreover, the analysis demonstrated that while biathletes generally seem to be concerned about the environment, their environmental concern does not seem to translate into pro-environmental travel behaviour, which can be explained by the fact that sustainable transportation represents a high-cost situation. Furthermore, some barriers were found to prevent elite athletes from travelling more sustainably. The barriers are related to individuality (other priorities - performance), responsibility (not athletes` responsibility) and practicality (national regulations regarding rifle transport in public transportation (PT)). However, many barriers were found to lie on a continuum between individuality and practicality. The most important of these barriers include travel time, equipment, exposure to other people or inconvenient PT system. Based on the findings, it was recommended to optimize schedules, which was found to be to be overall highly appreciated by biathletes. Some other recommendations include, for example, reservation of train compartments and/or special buses for biathletes and teams, communal equipment transportation between competition venues, vehicle provision at venues, or clear and updated information about regulations regarding rifle transport. These and other recommendations are believed to help biathletes to overcome some of their barriers and, thereby, encourage a more sustainable travel behaviour. Thereby, it is hoped that the knowledge gained in this thesis can help sport organizations and athletes to reduce the emissions from travelling to/from sport events.